Classification of damage to the structures of buildings in towns in coastal areas. (December 2016) - Adam, Jose M.; Moreno, Jose D.; Bonilla, Mercedes; Pellicer, Teresa M.
Abstract: Damage to the structure of buildings near the coast is often caused by the marine environment. This paper describes a study carried out on the state of the structures of buildings in towns near the coast in Valencia (Spain). The findings were based on inspections carried out on all the buildings in 14 towns considered representative of those in the area. A total of 1816 buildings were inspected, and the typical damage found in structures exposed to a marine environment was identified. The percentage of affected buildings was found to be quite high, in some cases over 40% of the total number in the town. Damage was classified into four levels of severity, and a significant percentage of structures were found to be gravely affected, requiring immediate repairs. Based on the experience acquired in these inspections, this paper proposes a tool that would allow the general state of buildings in coastal areas to be assessed by what is called a Global Damage Index . This tool can classify towns according to the predictable presence and level of structural damage to its buildings, and provides a preliminary assessment together with criteria for the measures to be taken, including access to finance from public bodies to cover the repairs, maintenance and protection of buildings. Highlights: Damage to the structure of buildings near the coast is often caused by the marine environment Habitual damage found in RC building structures in coastal zones are classified. 1816 buildings were inspected in order to evaluate damage in their structures. A high proportion of the buildings inspected (635 out of 1816) had structural damage. The Global Damage Index was defined to classify the general state of the buildings in a given town.